Pengaruh Motivasi Kerja dan Disiplin Kerja terhadap Prestasi Kerja Pegawai di Dinas Sosial Kabupaten Pesisir Selatan - Apria Siska Yendia; Aminar Sutra Dewi (MASALIQ, 2025)
This study aims to analyze the influence of work motivation and work discipline on employees’ job performance at the Social Service Office of Pesisir Selatan Regency. The analysis is grounded in the assumption that motivation and discipline are key factors determining the performance of public sector personnel in realizing organizational effectiveness. The research employed a quantitative approach with a survey design, involving 30 respondents comprising all employees of the Social Service Office of Pesisir Selatan Regency, selected using a saturated sampling technique. Data were collected through a closed-ended questionnaire and analyzed using multiple linear regression with SPSS. The results show that work motivation has a positive and significant effect on employees’ job performance, and work discipline likewise has a positive and significant effect on job performance. These findings reinforce McClelland’s motivation theory and Hasibuan’s concept of work discipline, and contribute to the development of human resource management scholarship, particularly in the governmental sector. Practically, the study underscores the importance of strengthening employees’ motivation and discipline as a strategic lever to enhance job performance and organizational productivity.